Pricing and Warranty Level Decisions for New and Remanufactured Short Life-Cycle Products - Gan Shu San; I Nyoman Pujawan (Jurnal Teknik Industri, 2017)
Remanufacturing has become more prominent as a recovery process to mitigate the massive disposal of short life-cycle product at its end-of-use. However, remanufactured product is often perceived to be inferior to new product, and it has lower value in consumer’s willingness to pay. To increase the perceived quality of the remanufactured product, manufacturer offers a warranty, since one of the three roles possessed in warranty is being a signal to product reliability. This paper studies the pricing decisions and warranty level decision for new and remanufactured products in a closed-loop supply chain consists of a manufacturer and a retailer. The optimization modeling is performed under Stackelberg game with manufacturer as the leader. We found that higher expansion effectiveness coefficient would increase the supply chain profit. Also, there is an interval of demand’s speed of change, where the total profit would be at its highest. The optimum warranty level can be achieved regardless the initial warranty level set at the beginning of retailer’s optimization. Furthermore, the remanufactured product’s wholesale and retail prices are influenced by the expansion effectiveness coefficient.